2023
DOI: 10.3390/foods12101982
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Industrial Modification on the Structure and Gel Features of Soy Protein Isolate and its Composite Gel with Myofibrillar Protein

Abstract: Native soy protein isolate (N-SPI) has a low denaturation point and low solubility, limiting its industrial application. The influence of different industrial modification methods (heat (H), alkaline (A), glycosylation (G), and oxidation (O)) on the structure of SPI, the properties of the gel, and the gel properties of soy protein isolate (SPI) in myofibril protein (MP) was evaluated. The study found that four industrial modifications did not influence the subunit composition of SPI. However, the four industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 99 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Specimens were processed following the protocol of Hu et al( Hu et al, 2023 ). Briefly, the prepared MP gels were cut into cuboids (0.5 cm × 0.4 cm × 0.3 cm), fixed with 2.5 % glutaraldehyde by volume for 2 d, and subsequently washed 3 times with phosphate buffer (pH 7.2) for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were processed following the protocol of Hu et al( Hu et al, 2023 ). Briefly, the prepared MP gels were cut into cuboids (0.5 cm × 0.4 cm × 0.3 cm), fixed with 2.5 % glutaraldehyde by volume for 2 d, and subsequently washed 3 times with phosphate buffer (pH 7.2) for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…By controlling the degree of glycosylation, the structure of HSPI-SOS conjugate can be altered, thereby enhancing the physical and chemical properties and stability of the gel. Hu et al (2023) evaluated the effects of different industrial modification methods (heat (H), alkali (A), glycosylation (G), and oxidation (O)) on the structure and gel properties of SPI. The study found that the four industrial modification methods did not affect the subunit composition of SPI.…”
Section: Gelation Propertymentioning
confidence: 99%
“…Hu et al. (2023) evaluated the effects of different industrial modification methods (heat (H), alkali (A), glycosylation (G), and oxidation (O)) on the structure and gel properties of SPI. The study found that the four industrial modification methods did not affect the subunit composition of SPI.…”
Section: Effect Of Glycosylation On Functional Properties Of Spimentioning
confidence: 99%